PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN ( STUDI KARYAWAN PADA NOZZ HOTEL SEMARANG) - Nurul Nurfita Sari, 13.05.51.0087; Indriyaningrum, Kis (Students Journal of Economic and Management, 2018)
This Research is a research that examines the influence of leadership, work environment and compensation on employeperformance at Nozz Hotel Semarang. This research aims to analyze the influence of leadership, work environment and compensation on employee performance at Nozz Hotel Semarang fifty six respondents are used in the research. Data collection methods used in this study is questionnaire method (questionnaire) by distributing a list of statement to respondents to obtain information. The data collected in the analysis used factor analysis to test the validity of item statement, cronbach alpha formula, to test the reliability of the instrument, regression analysis, to test the magnitude of the influence of each variable in the test with the coefficient of determination (R2) and partially prove each independent variable. While the result of his research are : (1) leadership does not have a positive and significant impact to employee performance (2) work environment has a positive and significant impact on employee performance (3) compensation does not have a positive and significant impact on employe performance.Keywords : work leadership, environment and compensation